Do you have COVID-19? How to increase the use of diagnostic and contact-tracing apps - Déborah Martínez; Cristina Parilli; Ana María Rojas; Carlos G. Scartascini; Alberto Simpser (Inter-American Development Bank (IDB), 2021)
Diagnostic and contact tracing apps are an important weapon against contagion during a pandemic. We study how the content of the messages used to promote the apps influences adoption by conducting a survey experiment on approximately 23,000 Mexican adults. Respondents were randomly assigned to one of three different prompts, or a control condition, before stating their willingness to adopt a diagnostic app and contact-tracing app. The prompt emphasizing government efforts to ensure data privacy, which has been one of the most common strategies, reduced willingness to adopt the diagnostic app by about 4 percentage points and the contact tracing app by 3 percentage points. An effective app promotion policy must understand individuals' reservations and be wary of unintended reactions to naive reassurances.
Keywords: D90; D91; D62; I12; 330; COVID19; Contact tracing apps; Diagnostic apps; Data privacy; Take-up; Priming